Fortified Foods Provide Varying Contributions to Iron, Vitamin a and Iodine Requirements of Women of Reproductive Age: Results from Coverage Surveys in 4 African Countries (P24-044-19). (13th June 2019) - Friesen, Valerie; Mbuya, Mduduzi; Neufeld, Lynnette; Wieringa, Frank
Abstract: Objectives: Data on the contribution of fortified foods to nutrient intakes of target populations are critical to design and evaluate performance of fortification programs. In this study we aimed to estimate actual and potential contribution of fortified foods to nutrient requirements of women of reproductive age (WRA) in 4 countries. Methods: Cross-sectional coverage surveys conducted in Nigeria (Lagos, Kano), South Africa (Gauteng, Eastern Cape), Tanzania and Uganda in 2015 collected data on household consumption of fortified foods and a sample of each food assessed if available. The amount of nutrient consumed daily from fortified foods was determined by multiplying the daily consumption of fortifiable food by WRA (determined by adult male equivalent method) by a fortification content. The median added nutrient content of all foods collected (based on individual sample analyses) was used. If both iron and vitamin A must be added to flour, iron was measured and vitamin A was estimated using iron content as a proxy assuming ratios followed standards. For potential estimates, the target nutrient content or 50% above the minimum content in the standard was used. The value was reported as a percentage of estimated average requirement (EAR) and/or recommended nutrient intake (RNI) of WRA for key nutrients accounting for combined nutrient intake from all fortified foods. Results: Fortified wheat, maize and/or semolina flours contribute minimally to iron needs (0–13% RNI) but have potential to contribute more if fortified to standard (5–64% RNI). Fortified oil, wheat and/or maize flours contribute moderately to vitamin A needs in South Africa, Tanzania and Uganda (30–41% EAR; 15–30% RNI) with potential to contribute more if fortified to standard (61–102% EAR; 44–73% RNI). Fortified flours, oil and sugar nearly reach or exceed vitamin A needs in Nigeria (105–125% EAR; 75–89% RNI) and would greatly exceed needs if fortified to standard (299–649% EAR; 213–563% RNI). Fortified salt nearly meets or exceeds iodine needs (102–272% EAR; 73–194% RNI) with potential to contribute more if fortified to standard (115–283% EAR; 82–254% RNI). Conclusions: Fortified foods provide varying contributions to nutrient requirements of WRA even when standards are not met. Excessive intakes of vitamin A in Nigeria and iodine in all 4 countries is a concern. Funding Sources: Bill & Melinda Gates Foundation.